Ruptured Brain Aneurysm: A Rare Cause Of Isolated Acute Subdural Hematoma - Simon-Pierre Docquier; Thomas Bonnet; Boris Lubicz (Journal of the Belgian Society of Radiology)
Teaching point: Although computed tomography (CT) is the diagnostic gold standard for acute subdural hematoma, the absence of clear trauma should prompt the use of computed tomography angiography (CTA) to identify potential underlying causes, such as ruptured aneurysms, which can significantly influence treatment decisions.